Three new species of the genus Krisna Kirkaldy (Hemiptera: Cicadellidae: Iassinae) from China, with a checklist of the genus - Zhang, Yalin; Zhang, Xinmin; Dai, Wu (Zootaxa, 2008)
Eight species of the genus Krisna Kirkaldy from China including three new species are recognized: Krisna concava Li & Wang, K. furcata sp. nov., K. nigromarginata Cai & He, K. rufimarginata Cai & He, K. strigicollis (Spinola), K. viridula Li & Wang, K. daiyunensis sp. nov., K. viraktamathi sp. nov. Two new synonyms are revealed, Krisna bimaculata Cai & He, 1998 syn. nov., a junior synonym of Krisna concava Li & Wang, 1991 and Krisna burmanica Viraktamath, 2006 syn. nov., a junior synonym of Krisna rufimarginata Cai & He, 1998. A key is proposed to ten Chinese species. Detailed morphological descriptions and illustrations of eight species are given and a checklist of all known species of the genus is also provided.